Technical Analysis of the ETCS Architecture Development - GENG Hongliang; ZHANG Chao; SUN Ye; LI Qihe; KE Changbo; LIU Zhenyu (Kongzhi Yu Xinxi Jishu)
Specifications of European train control system (ETCS) were released in 2016 as baseline 3(3.6.0), and it has been continuously developed and improved through projects such as TEN-T, NGTC and Shift2Rail. In recent years, on the basis of maintaining the characteristics of interoperability, the system has defined new functions, including level crossing control, improved braking model and automatic train operation. At the same time, it keeps the compatibility to the existing system. In this paper, it analyzed the updates for the process, architecture, functions and technology trends. Hopefully, such analysis could be helpful for the CTCS development, and the interoperability between CTCS and ETCS.